Kalender Hijriah Global Tunggal dan Tantangan Penerapannya di Indonesia - Aspar; Sumartini; Muktashim Billah (Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the concept of the Global Unified Hijri Calendar (KHGT) and analyze the challenges of its implementation in Indonesia. This research employs a library research method by reviewing various literature sources such as books, journal articles, and scientific documents related to the Hijri calendar, Islamic astronomy, and the concept of Islamic calendar unification. The findings indicate that KHGT is an Islamic lunar calendar system designed to unify the determination of Hijri dates worldwide based on the principle of one day–one date globally. This system utilizes astronomical calculations (hisab) with specific parameters such as moon altitude and elongation as agreed upon in the 2016 Istanbul Conference. Although KHGT has strong scientific and sharia foundations, its implementation in Indonesia still faces several challenges, including differences in the use of hisab and rukyat methods, differing views on the concept of matla’, and socio-religious traditions within the Muslim community. Therefore, continuous dialogue, socialization, and further studies are necessary to support broader understanding and potential implementation of the global Hijri calendar in the future.